The Effect of a Knowledge-Based Intervention on the Use of Respirators in the Norwegian Smelter Industry - Robertsen, Øystein (Front Psychol, 2020)
INTRODUCTION: The present study investigated the effect of interventions aiming to improve attitudes toward the use of respiratory protective equipment (RPE), knowledge of RPE and the use of RPE in the Norwegian smelter industry. METHOD: The surveys received 567 respondents to baseline and 240 respondents 2 weeks after the intervention. Participants were invited to either a fit-testing of respirators [Group 1] or a fit-testing combined with a lecture on exposure [Group 2], health effects and RPE. The control group [Group 3] received no training. Questionnaires containing measures of subjective knowledge, attitudes and behavior regarding RPE use were assessed. RESULTS: Testing indicated an improvement in knowledge of RPE and a reduction in perceived inconveniences regarding the use of RPE for both intervention groups. Group 1 showed an improvement in attitudes and organizational support, while intervention Group 2 showed an improvement in subjective norms related to RPE use. Intention to use or rate of respirator use was not shown to change significantly for any group using paired testing. Regression analysis indicated that participation in either intervention influenced intention to use respirators. The effect was significant for Group 1 and was marginally significant for intervention Group 2. CONCLUSION: The results indicate that interventions can increase workers’ knowledge and attitudes, and reduce perceived inconvenience regarding the use of respiratory protective equipment. However, even though some variables seemed to positively change, reported respirator use did not improve for either groups participating in the study. It may be that physical barriers with regards to using RPE, such as fogging of protective goggles, sweating, breathing and communication issues outweigh individual attitudes, intentions and social pressure to use respirators. PRACTICAL APPLICATIONS: The tailored course and practical training in RPE use in the current intervention can be applied in the smelting industry to provide up to date information on dust exposure, health effects and protective equipment. Some adjustments may be warranted for the content to fit specific risks and exposures of other industries. However, the general pedagogical framework of the educational material regarding health effects and RPE should be useful for most heavy industries.